2012
DOI: 10.1159/000342905
|View full text |Cite
|
Sign up to set email alerts
|

Audiological Follow-Up of Children with the m.1555A>G Mutation in Mitochondrial DNA

Abstract: The age at onset and the severity of hearing impairment (HI) varies widely among subjects and within families with the m.1555A>G mutation in mitochondrial DNA. We examined prospectively the hearing of 19 children in three nuclear families of a pedigree with m.1555A>G during a period of 7.8 years. The children underwent an audiological examination annually. At the end of the follow-up, the children were 2–13 years old. The parents were asked about the exposure of the children to risk factors of HI. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…Interestingly, the majority of those with homoplasmic status, comparable with our group, demonstrated early onset of hearing loss at between 1 and 5 years of age. Analogous results were presented by Hakli et al [ 23 [. Chen Chi Wu et al reported 30 individuals with hearing loss caused by the m.1555A>G mutation [ 9 ] and found early onset of hearing loss in 23 of them (in 8 individuals under 10 years of age, in the remaining 15 between 10 and 20 years of age).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the majority of those with homoplasmic status, comparable with our group, demonstrated early onset of hearing loss at between 1 and 5 years of age. Analogous results were presented by Hakli et al [ 23 [. Chen Chi Wu et al reported 30 individuals with hearing loss caused by the m.1555A>G mutation [ 9 ] and found early onset of hearing loss in 23 of them (in 8 individuals under 10 years of age, in the remaining 15 between 10 and 20 years of age).…”
Section: Discussionsupporting
confidence: 89%
“…Her HI progressed to be severe by age 10.2 years and she received a cochlear implant at age 11.3 years. Her mother and five of her eight siblings had HI [ 23 ]. In this pedigree we were able to ascertain four children with HI, who harboured m.1555A > G and who had been born between the years 1993–2002 in Northern Finland.…”
Section: Resultsmentioning
confidence: 99%
“…However, family studies of m.1555A>G carriers indicate a very high penetrance of permanent hearing loss if aminoglycosides are given [ 5 ], and a recently published follow up study including 19 Finish m.1555A>G carriers reported that all children passed the newborn hearing screening, but 10 of 19 developed permanent hearing loss at a median age of 3.7 years [ 15 ]. Therefore, our current data might considerably underestimate the long term effect of the aminoglycoside use in preterm infants carrying m.1555A>G.…”
Section: Discussionmentioning
confidence: 99%